Investment-centric innovation project management : winning the new product development game - Keays, Steven, 1963- (J. Ross Publishing, Inc., 2018)
A survival pack to be used on your journey through the innovation landscape, this book provides the knowledge and grit needed to overcome the numerous obstacles that innovators will face in what many are calling the golden age of automation and artificial intelligence. --